Antimicrobial resistance in a protracted war setting: a review of the literature from Palestine - Kumar, Ramya; Tanous, Osama; Mills, David; Wispelwey, Bram; Asi, Yara; Hammoudeh, Weeam; Dewachi, Omar (mSystems, 2025)
This study goes beyond merely reviewing and summarizing data on AMR in the occupied Palestinian territories (oPt), a region enduring chronic war-like conditions. Our work addresses critical gaps in knowledge about AMR in populations affected by war and siege. By contextualizing AMR through a socio-political lens, this study offers a novel perspective. It highlights deeper drivers, including the impact of war on the behaviors and education of patients and doctors, perceptions of antibiotics, the role of humanitarian interventions in fostering antibiotic anarchy, and the overall weakening of the Palestinian healthcare system. Importantly, this review also sets the stage for understanding the existing literature on AMR in the oPt within the context of the ongoing war in Gaza, emphasizing the immediate need for comprehensive strategies to address AMR under conditions of conflict. The insights can inform physicians and policymakers in designing and implementing effective AMR stewardship programs, not only in Palestine but also in other conflict-affected regions.